Understand Fiscal Decentralization and the Potential Moral Hazard in Indonesia - Ahmad Fadhil Imran; Basri Bado; Hafid Sumarwadji (LPPM Universitas BSI, 2023)
Fiscal decentralization as a product form of political economy policy is a determinant of a country's economic growth. However, the implementation of these policies is considered vulnerable due to a lack of transparency and accountability, so that abuse of authority at the local government level often occurs which causes moral hazard and triggers fiscal policy inefficiencies. We describe the search related to fiscal decentralization through this research and how the potential for moral hazard can occur in Indonesia. This type of research is a literature study using a descriptive qualitative approach. The data collected is in the form of results from literature reviews, journals, books, newspapers, and documentation that are considered relevant. After reviewing, criticizing, and synthesizing representative literature in such a way, we are able to find several facts indicating that fiscal decentralization can be a solution to overcome economic inequality, on the other hand it can also be utilized by various parties for personal gain. With various polarizations built by the authorities, moral hazard has the potential to occur at any time.